Microbiota-dependent metabolites – New engine for T cell warriors - Yang Tang; Anbo Fu; Liangjing Wang; Qiwei Ge (Gut Microbes)
Microbiota-dependent metabolites (MDMs) are small bioactive molecules produced or modified through microbial metabolic processes, playing an essential role in the communication between prokaryotic and eukaryotic cells. One of their most important roles is their regulatory effects on the immune system, particularly in shaping the development, differentiation, and function of T cells, which are key players in the adaptive immune response. Emerging research highlights those microbial metabolites, such as short-chain fatty acids (SCFAs), tryptophan-derived metabolites, and bile acids (BAs), modulate T cell responses in both health and disease contexts, impacting conditions ranging from autoimmune disorders to cancer. This review summarizes current advances in deciphering MDMs that critically regulate T cell function and elucidating their biosynthetic origins and mechanisms underlying immunomodulation and pathogenesis. Furthermore, we highlight the application of emerging technologies—in vitro bioreactors and organ models, genetic manipulation, and chemical proteomics – in delineating dynamic crosstalk between MDMs and immune signaling networks. We discuss future research perspectives in this field, emphasizing the need for more in-depth mechanistic studies and research strategies from an ecological approach will facilitate the clinical translation of MDMs.